Encouraging or expecting flexibility? How small business leaders' mastery goal orientation influences employee flexibility through different work climate perceptions. (December 2022) - Solberg, Elizabeth; Sverdrup, Therese E; Sandvik, Alexander Madsen; Schei, Vidar
The employee flexibility desired in changing and uncertain business environments is amplified in small business settings. How can small business leaders facilitate the employee flexibility needed in this context? In the present study, we proposed that mastery goal-oriented leaders who are concerned with learning and competence development would create a work climate that promoted employee flexibility in their firms. We tested our hypotheses with multi-wave, multi-level data collected from leaders and employees in 141 small accounting firms in Norway. Findings revealed that leaders' mastery goal orientation (MGO) was positively related to employee flexibility through a work climate that encouraged learning and development (a mastery climate). Yet, we also found that leaders' MGO was negatively related to employee flexibility through a work climate that emphasized the expectations to be adaptive and flexible (an adaptability climate). Taken together, our study suggests that leaders' mastery goal orientation may fuel employee flexibility when encouraging flexible-related behavior yet backfire when they signal that the same behavior is expected.